KEYNOTE 1. Healthy Moves: Exploring the Socio-Ecological Approach to Active Transport – How Far Can We Go Together (Baltic Journal of Sport and Health Sciences, 2026)
Climate change has underscored the critical need for society to adopt sustainable behaviours – actions that promote health whileminimising negative impacts on the planet. Among these, ‘high-impact’ health-related behaviours, such as active transport, standout for their signifcant eﬀects on greenhouse gas (GHG) emissions.The health and environmental benefts of physical activity are deeply interconnected and are reﬂected in the 2030 Agenda forSustainable Development (United Nations General Assembly, 2015). Beyond improving individual health, a society that embraces active transport also enjoys additional advantages: reduced fossil fuel consumption, cleaner air, less trafc congestion,and safer roads. Thus, active transport contributes to public health in at least two distinct ways – by enhancing individual healthand longevity, and by improving environmental health, which in turn has secondary benefts for individuals, oﬀering a ‘doublebeneft’.An individual’s behaviour is shaped and established within their social environment – family, peers, organisations, and theprevailing social norms. In addition, broader environmental factors, such as infrastructure that supports active transport, play acrucial role in fostering behaviours that beneft both health and the environment.In response to the UNESCO Sustainable Development Goals and the societal changes driven by climate change, this presentation aims to highlight the importance of individual, interpersonal, organisational, and community factors that enable or hinderactive transport. The analysis is grounded in a socio-ecological approach, examining factors both within and across the diﬀerentlevels of the socio-ecological model.This presentation is based on the premise that empowering society to transform is closely linked to human factors and socialconnections. By manipulating these elements – such as rules, norms, and cooperation – across all levels, including institutional(legislation), organisational, and interpersonal, it is possible to signifcantly accelerate the shift towards more sustainable behaviours, step by step